Pertumbuhan dan hasil panen Bawang Merah (Allium ascalonicum l.) akibat penambahan pupuk KCl berbasis pupuk organik berbeda - Neli Afrilliana; Adriani Darmawati; Sumarsono Sumarsono (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
The research aims to determine the effect of KCl addition on the growth and yield of shallot (Allium ascalonicum L.) on various organic fertilizer bases. The research was conducted using a monofactor experiment with Randomized Completely Block Design (RCBD) consisting of 8 treatments with four replications. The treatment is without fertilization (K0), chicken manure (K1), goat manure (K2), cattle manure (K3), chicken manure + KCl (K4), goat manure + KCl (K5), cattle manure + KCl (K6), Urea, SP-36, KCl (K7). The observed parameters are plant height, leaf number, bulb number, bulb diameter, wet weight of plant and the potassium (K) uptake of plant. Data were subjected to Analysis of Variance (ANOVA) and followed by Duncan Multiple Range Test (DMRT). The results of the research showed organic fertilizer with or without KCl addition or NPK fertilizer gave higher plant height, leaf number, bulb diameter and wet weight of plant and potasium (K) uptake compared to without fertilization. The KCl addition on organic fertilizer did not increase wet weight of plant. The treatment chicken manure gave the higher indication on yield of plant compare to goat and cow manure.Keywords: shallot, organic fertilizer, KCl